MELIHAT KEPUASAN HIDUP GURU NON-PNS BERDASARKAN DUKUNGAN SOSIAL DAN KEBERSYUKURAN - Fathurrahman, Farouq (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Social support and gratitude are among the factors that can affect life satisfaction among non-civil servant teachers. Social support can be important because it can increase the gratitude of a teacher and the higher of these two things can increase the life satisfaction of the teacher. The purpose of this study was to see the effect of social support and gratitude on life satisfaction among non-civil servant teachers. This study involved 75 non-civil servant teachers who were obtained using purpos-ive sampling technique. The data analysis used in this research is multiple regres-sion. The results of this study, that social support and gratitude have a joint influ-ence on life satisfaction in non-civil servant teachers. In particular, the effect of gratitude is slightly greater than social support.